PEMBINAAN MENTAL BERBENTUK SCAFFOLDING BAGI GENERASI MILENIAL: Mental Coaching In The Shapes Of Scaffolding For The Millennial Generation - Patintingan, Mersilina Luther; Hakpantria; Gemil (Forind Press, 2023)
The millennial generation is a group of people who are dependent on information and communication technology. Because this time span is the time span when the world began to introduce and develop various modern technologies including information and communication technology to make it easier for humans to achieve goals in every activity of their lives. Mental coaching for the millennial generation is very necessary, so that the millennial generation, especially for new PGSD students in the 2022/2023 academic year, how to get to know the campus world, attitudes and behaviour as students, this can be done through mental coaching. Millennial generation scaffolding needs are a need for mental coaching for new Millennial Generation Teacher Education (PGSD) students in the 2022/2023 academic year. The purpose of this research is to provide mental coaching in the form of scaffolding to the millennial generation, especially to early students who have just enjoyed campus life and do not necessarily have certainty about self-concept and identity. The implementation method is divided into 3 (three) stages: Apperception, Constructing, Mentoring. From this mental coaching method in the form of Scaffolding, the results were obtained: there were 71% of participants who learned to develop Problem Solving Skills, there were 56% whose communication skills improved.